Study of power-hardware-in-the-loop experiment for lithium-ion battery testing - Ang, ShangSheng (Nanyang Technological University, 2020)
The massive growth in development and population in countries over the world led to an increase in demand of electricity needs. It causes non-renewable natural resources to be slowly depleted and worsens global warming. Exploration of alternative sources of energy like harvesting electricity from solar energy is critical. With the improvement of technology, it allows OPAL-RT to be readily equipped with advanced electronic devices making the Real-Time Digital Simulator (RTDS) possible. This research uses RTDS as a simulation platform to simulate actual electrical systems and forecast realistic real-time output of the system. Using the digital and analogue interfaces from OPAL-RT, it establishes communications between the virtual and actual components allowing part of the system to be tested under a more controlled and safer environment. However, existing experiments with OPAL-RT in NTU were either integrated with dSPACE or a power amplifier but never both simultaneously. In addition, despite numerous amounts of literature on direct current (DC) microgrids, there is a lack of research in a systematic method to ensure stability in the DC microgrid system during uncertain constant power loads (CPLs). Through this project, documentation of the insights and results of RTDS facilitates power hardware in the loop (PHIL) testing with the integration of the Spitzenberger & Spies (S&S) power amplifier as well as Control Hardware in-the-Loop (CHIL) testing by integrating dSPACE into a simulated DC microgrid system in the OPAL-RT. The PHIL experiment will be simulated with a varying load demand and the renewable energy generation. Hence, the PHIL simulation does not just test out the physical hardware, it also assists in the study of the unique and interesting approach to handling fluctuation of load demands.